Berziarah dalam Dunia yang Kompleks dan Plural: Peran Situs dan Praktik Ziarah Katolik dalam Misi Evangelisasi Gereja - Albertus Bagus Laksana; William Christopher Hariandja; Rezerius Bintang Taruna (Indonesian Journal of Theology, 2023)
Through case study research involving several Catholic pilgrimage sites in Java and Bali, this article shows the role of Catholic pilgrimage sites and their assoiated practices. By taking a phenomenological-anthropological approach informed by sacramental theology and a Catholic theology of evangelization, this article examines today’s dynamics of evangelization in an increasingly divided, complex, and pluralistic era. Pilgrimage sites and traditions have a unique role in the process of evangelization, understood as an expansion of the Church’s presence that transforms people and local communities, with pilgrimage sites and practices shown to empower pilgrims by helping them connect with God, themselves, others, and the universe on a personal, spiritual level. The administrators of pilgrimage sites also seek solidarity with a site’s surrounding community. Given that the Catholic pilgrimage tradition helps people to express their religion in personal, interpersonal, cosmic, and inclusive ways vis-à-vis other religions, the pilgrimage tradition helps the Church and society face the dangers of the privatization of religion, the politicization of religion, and the spread of radical and iconoclastic ideologizations of religion. Such is the task of contextual evangelization in a plural and complex society like Indonesia.